Algorithmic decision theory Second International Conference, ADT 2011, Piscataway, NJ, USA, October 26-28, 2011. Proceedings - Brafman, Ronen I.; Roberts, Fred S.; Tsoukiàs, Alexis; SpringeringerLink (Online services). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Algorithmic Decision Theory, ADT 2011, held in Piscataway, NJ, USA, in October 2011. The 24 revised full papers presented were carefully reviewed and selected from 50 submissions.
Electronic reproduction.
Keywords: Computer science; Computer software; Artificial intelligence; Automatic theorem proving -- Congresses; Computer algorithms -- Congresses; Decision making -- Data processing -- Congresses; Electronic books